গণমানুষের অর্থনীতিবিদ আবুল বারকাত - Caudhurī, Āśarāpha Uddina (ঢাকা : অর্থসংবাদ প্রকাশনা, 2014)
Contributed articles on the life of Abul Barkat, renowned economist from Bangladesh.
গ্রন্থপঞ্জিগত নির্দেশিকা (পৃষ্ঠা ৮০২-৮৭৫) ও নির্ঘণ্ট অন্তর্ভুক্ত।
Donated By Akbar Ali Khan
In Bengali; includes passages in English.
Keywords: Barkat, Abul; Economists -- Bangladesh -- Biography; Economists -- Bangladesh